2017
DOI: 10.1080/16549716.2017.1328168
|View full text |Cite
|
Sign up to set email alerts
|

A smartphone-based consultation system for acute burns – methodological challenges related to follow-up of the system

Abstract: Background: A smartphone-based consultation system for acute burns is currently being implemented in the Western Cape, South Africa. Even though studies indicate that similar systems for burns tend to support valid diagnosis and influence patient management, the evidence is still sparse. There is a need for more in-depth evaluations, not least in resource-constrained settings where mHealth projects are increasing. Objective: This article describes the consultation system and assessments in relation to its impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…For instance, although there are numerous examples of teleconsultation in other medical specialties, [24] there appeared to be little existing literature on mHealth in orthopaedics referrals. Previous studies relating to the Vula app have focused on considerations around its use for burn referrals [15,17] and did not report outcomes such as referral distribution and referral outcome as in the current study. It is noted, however, that qualitative research on expectations around the app identified a possible role for education through Vula [15] -a suggestion supported through evidence of upskilling in some of the current referrals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, although there are numerous examples of teleconsultation in other medical specialties, [24] there appeared to be little existing literature on mHealth in orthopaedics referrals. Previous studies relating to the Vula app have focused on considerations around its use for burn referrals [15,17] and did not report outcomes such as referral distribution and referral outcome as in the current study. It is noted, however, that qualitative research on expectations around the app identified a possible role for education through Vula [15] -a suggestion supported through evidence of upskilling in some of the current referrals.…”
Section: Discussionmentioning
confidence: 99%
“…Further details of the app and considerations around its use for burn referrals have been published elsewhere. [15,17] In August 2016, the Division of Orthopaedic Surgery at Tygerberg Hospital was the first orthopaedic department to introduce referrals via the app, and awareness of this new referral option was specifically promoted through visits to key health facilities in the hospital's referral network. In theory, Vula had several advantages over traditional phone-based referrals.…”
Section: Researchmentioning
confidence: 99%
“…Password-protected phones and restricted communication about patient management could be used to protect confidentiality. 25,31 Other mHealth applications, such as Vula Mobile, censor identifying information except to the referring clinician 32 and should be considered for future use by ORG. Limitations in data collection did not allow for further stratification of fracture cases.…”
Section: Discussionmentioning
confidence: 99%
“…Costs of burn care could potentially be reduced even further by using pre-existing smartphones, as they don't require significant investment in new technology and might increase the utility of telemedicine even further. 18 Moreover, improved utilization of technology has the potential to reduce overtriage and improve pre-arrival care. While telemedicine would mitigate some of the inequities of burn care delivery, it fails to address the underlying problem-lack of burn education.…”
Section: A Disaster Waiting To Happenmentioning
confidence: 99%